The Ascent of Money and Social Transformation Among the Badeng of Sarawak - Tan, Chee-Beng (Cultural and religious studies, 2020)
This article examines the Badeng Kenyah, a people in Sarawak’s interior who are experiencing the shift from subsistence living to a money economy. Ethnographic description and oral history are used to examine the inside factors (such as the individual search for livelihood) and outside forces (government and the market) that brought about this shift. Some philosophical reflection addresses the impact of money on individuality and social life, with inspiration drawn from the classic works of Karl Polanyi and Georg Simmel. When the myth of money becomes accepted as a norm, human self-interest naturally guides individual behavior toward commodification, a path negotiated through those moral values that a community has maintained intact and those it has redefined to suit a monetary economy. For better and for worse, commodification works vast changes on social relations and the environment. What the Badeng experienced is what all modern peoples have gone through at one point or another. By looking at what happened to these particular people, we see again the experience that has shaped us all.